2017
DOI: 10.1007/s11356-017-0281-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of manures to mitigate the harmful effects of electrokinetic remediation of heavy metals on soil microbial properties in polluted soils

Abstract: Ethylenediaminetetraacetic acid (EDTA) used with electrokinetic (EK) to remediate heavy metal-polluted soils is a toxic chelate for soil microorganisms. Therefore, this study aimed to evaluate the effects of alternative organic chelates to EDTA on improving the microbial properties of a heavy metal-polluted soil subjected to EK. Cow manure extract (CME), poultry manure extract (PME) and EDTA were applied to a lead (Pb) and zinc (Zn)-polluted calcareous soil which were subjected to two electric intensities (1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 77 publications
(96 reference statements)
1
4
0
Order By: Relevance
“…Soil pH may regulate soil aggregation through influencing plant growth, metal ion solubility, microbial activity, and clay dispersion (Haynes and Naidu 1998;Tahmasbian et al 2017). Consistently, our analyses reported that changes of soil pH were tightly related to variations of soil aggregate MWD (Table 2; Fig.…”
Section: Effects Of Forest Succession On Soil Aggregationsupporting
confidence: 81%
“…Soil pH may regulate soil aggregation through influencing plant growth, metal ion solubility, microbial activity, and clay dispersion (Haynes and Naidu 1998;Tahmasbian et al 2017). Consistently, our analyses reported that changes of soil pH were tightly related to variations of soil aggregate MWD (Table 2; Fig.…”
Section: Effects Of Forest Succession On Soil Aggregationsupporting
confidence: 81%
“…It is known that SOC decreases in long-term PTM-polluted soils (Viventsova et al 2005), but soil washing of contaminated soils may also have negative effects on SOM. Many studies have reported that after soil washing with Na 2 EDTA, the SOM did not change (Zupanc et al 2014;Tahmasbian et al 2017;Hosseini et al 2018). Sometimes, changes in SOC are difficult to investigate because these changes occur slowly and are relatively small compared to the vast SOC pool size, but some of the soil C fractions, such as humic acids, are more sensitive than the total SOC (Slepetiene et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that SOC decreases in long-term PTM-polluted soils (Viventsova et al 2005), but soil washing of contaminated soils may also have negative effects on SOM. Many studies have reported that after soil washing with Na 2 EDTA the SOM did not change (Zupanc et al 2014; Jelusic et al 2014;Hu et al 2014;Tahmasbian et al 2017;Hosseini et al 2018). Sometimes changes in SOC are di cult to investigate because these changes occur slowly and are relatively small compared to the vast SOC pool size, but some of the soil C fractions, such as humic acids, are more sensitive than the total SOC (Slepetiene et al 2011).…”
Section: Introductionmentioning
confidence: 99%